A MULTI-OBJECTIVE APPROACH TO THE EVALUATION OF INNOVATIVE POTENTIAL OF THE TOURISM INDUSTRY ORGANIZATIONS - Tat’yana Pavlovna Levchenko (International Journal of Advanced Studies, 2018)
Speaking about innovation in the tourism industry and hotel business, in particular, it usually means events of a systemic nature, with quality novelty, aimed at achieving positive changes, stable functioning and dynamic development. Along with general economic factors that determine the uneven demand for services of hospitality, it is explained by the sharp increase in dependence of their tourism and recreational opportunities from innovative potential (IP), capability of adapting to challenging competitive environment.